INVESTMENT MARKETING: TECHNIQUES AND METHODS OF IMPLEMENTATION IN THE FINANCIAL POLICY OF THE ORGANIZATIONS - E. Gulkova; L. Kazimirova (Вестник университета)
The possibility of applying marketing technologies in the conditions of realization of investment projects when the financial-economic policy of Russian enterprises at the present stage are discussed. The analysis of existing methods of investment marketing in the Russian Federation taking into account the potential development of the main methods used by Russian investors is considered. The means of evaluating the effectiveness of investments in marketing in order to monitor ongoing marketing activities for timely adjustments to the selected strategy and financial policy of the company are dedicated and systemated. The main directions of the development and assessment of marketing potential investments for the creation of new spheres of production and spheres of maintenance, reconstruction and upgrading of existing industries are defined.